Quantifying the association between stroke and dementia: a bibliometric study - Bian, Xinyi; Zhao, Zibin; Gao, Xiaoping (Frontiers in Neurology, 2024)
Background Stroke and dementia are two serious neurological disorders in modern medicine. Studies have revealed a significant link between the two, but there is still a lack of bibliometric analysis in this area. The objective of this study is to use bibliometric analysis to investigate the connection between stroke and dementia, as well as to assess the current state of research in this field and identify future trends. Methods The publications from the Web of Science were Collection and retrieved for the last 22 years (2002–2023). CiteSpace, VOSviewer, and the R package Bibliometrix were used to conduct bibliometric analysis. GraphPad Prism was used to plot. Results A total of 1,309 publications were included in the analysis. The number of articles on dementia and stroke has continued to grow steadily over the past 22 years. While China is the country with the most articles, the most influential and widely researched countries are England and the United States. The keyword analysis illustrates that the prevention of dementia through stroke prevention is a major focus and trend in this research area. Conclusion This study provides a visual analysis method for measuring the association between stroke and dementia, and examines the current state of research in this area and future research trends. In the future, dementia caused by stroke needs to be emphasized, and prevention of dementia through stroke prevention is a research priority.